GRA W NAZYWANIE Z PREFERENCYJNYM WYBOREM PARTNERÓW - Lipowska, Dorota (Investigationes Linguisticae, 2012)
In this paper, a naming game on an adaptive weighted network is examined. A weight of connection for a given pair of agents depends on their communication success rate and determines the probability with which the agents communicate. When the preference toward successfully communicating agents is not so strong, the model behaves similarly to the naming game on a complete graph. In particular, it quickly reaches a single-language state, albeit some details of the dynamics are different from the complete-graph version. Much different behaviour appears when the preference toward successfully communicating agents is stronger and the model gets trapped in a multi-language regime. In this case gradual coarsening and extinction of languages lead to the emergence of a dominant language, albeit with some other languages still being present. A comparison of distribution of languages in the model and in the human population is discussed.